2013
DOI: 10.1186/2052-4374-25-22
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Tracheal Adenoid Cystic Carcinoma in a Worker Exposed to Rubber Fumes

Abstract: BackgroundPrimary tracheal tumors occur infrequently, accounting for less than 0.1% of all tumors. Adenoid cystic carcinoma (ACC) is the second most common type of malignancy of the trachea after squamous cell carcinoma (SCC). Little has been reported on the risk factors for tracheal ACC. The purpose of this study is to describe a case of tracheal ACC in a patient who had been exposed to rubber fumes, and to review the relationship between tracheal ACC and rubber fumes.Case reportA 48-year-old man who had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…1,8 ACC's have been reported without sex predilection in patients in the fifth decade of life; our patients are 49 and 50 years old; and smoking does not affect the incidence of ACC. 3,4 Patients with ACC usually present with symptoms such as coughing, wheezing and dyspnoea and are often treated for asthma for months to years before being correctly diagnosed1, as in our second patient. ACC is none capsulated tumour, it spreads most commonly by direct extension, submucosal or perineural invasion, in transverse and longitudinal planes.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…1,8 ACC's have been reported without sex predilection in patients in the fifth decade of life; our patients are 49 and 50 years old; and smoking does not affect the incidence of ACC. 3,4 Patients with ACC usually present with symptoms such as coughing, wheezing and dyspnoea and are often treated for asthma for months to years before being correctly diagnosed1, as in our second patient. ACC is none capsulated tumour, it spreads most commonly by direct extension, submucosal or perineural invasion, in transverse and longitudinal planes.…”
Section: Discussionmentioning
confidence: 88%
“…ACC is none capsulated tumour, it spreads most commonly by direct extension, submucosal or perineural invasion, in transverse and longitudinal planes. 4,5 Lymphatic spread is uncommon. More than 50 % of patients with tracheal ACC have haematogenous metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiological risk factors for all salivary gland malignancies include exposure to nickel compounds and silica dust, employment at rubber manufacturing, hairdressers´, and beauty shops, as well as irradiation, EBV, and HIV infection [10, 28, 29]. At molecular level, germline BRCA mutations and genetic variants in DNA double-strand brake repair genes have been related to the risk for salivary gland cancers including ACC [3].…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study reported the carcinogenic susceptibility of salivary glands to nitrosamine [ 68 ]. It has also been reported that the workers exposed to nitrosamine have a higher mortality rate from salivary gland carcinoma [ 69 ].…”
Section: Pathology Of Salivary Glandsmentioning
confidence: 99%